CA-IDTIMS and biostratigraphy: Their impact on exploration. Issue 1 (1st December 2018) - Laurie, John; Smith, Tegan; Bodorkos, Simon; Nicoll, Bob; Crowley, Jim; Mantle, Dan; Wood, Geoff
Abstract : Uranium-Lead dating of Zircon using the Chemical Abrasion-Isotope Dilution Thermal Ionisation Mass Spectrometry (CA-IDTIMS) technique has largely overcome the problem of radiogenic lead loss, and has greatly improved the precision of the dating. That improvement in precision and the plethora of tuffs throughout the Permian and Triassic successions in eastern Australian basins (Tasmania, Sydney, Gunnedah, Bowen and Galilee) permits the recalibration of the Australian spore and pollen palynostratigraphic scheme directly to the numerical timescale, obviating the need for a multi-step process of correlation. The Permian recalibration has, for example, shown the base of the Dulhuntyispora parvithola (APP5) Zone to be about 6 million years younger than previously calibrated, and in the Triassic, the base of the Polycingulatisporites crenulatus (APT5) Zone could be about as much as 10 million years younger than previously calibrated.